Current antiseptics: a study on their antimicrobial activity and toxic effects on the corneal epithelium (Ukrainian Journal of Ophthalmology, 2025)
Background: Infectious agents can develop resistance to antibiotics, but antiseptics maintain their efficacy. It is still important to enhance our understanding of the effects of antiseptics on the macroorganism.Purpose: To investigate antimicrobial efficacy of the current antiseptic medications used in the ophthalmological practice, quaternary ammonium compounds (QACs) of decamethoxin (oftalmodek or OD) and miramistin (okomistin or OM), and to assess their effects on anterior corneal epithelial (ACE) DNA fragmentation and cell cycle in rats.Methods: We conducted a microbiological study to compare OD and OM for antimicrobial efficacy using serial two-fold dilutions. In addition, flow cytometry was used to investigate the effects of these medications on ACE cell apoptosis and proliferation in rats.Results:  When compared with OM, OD demonstrated a higher antimicrobial efficacy against a wide spectrum of infectious agents (р < 0.001). Our in vivo flow cytometry study found no significant difference (p > 0.05) in fractions of ACE cells in various cell cycle phases between experimental eyes that received OD and intact fellow eyes. Experimental eyes in the okomistin group demonstrated depressed DNA synthesis in nuclei of ACE cells, with the fraction of ACE cells in the S phase that was 1.4-fold lower (р < 0.05) than in intact fellow eyes. In addition, the fraction of ACE cells in the G2+M phase and proliferative index of the ACE were 1.4-fold and 1.6-fold, respectively, lower (р < 0.05),  whereas DNA fragmentation level in ACE cell nuclei was 1.5-fold higher (р < 0.05) than in intact fellow eyes.Conclusion: Oftalmodek has high antimicrobial activity against a broad spectrum of infectious agents and has no cytotoxic or proapoptotic effects.  This was evidenced by the respective indices of its activity, which were 1.8 to 6.1-fold higher than those of okomistin (р < 0.001). However, the use of okomistin resulted in depressed DNA synthesis in nuclei of ACE cells, decreased proliferative index of the ACE, and increased DNA fragmentation level in epithelial cell nuclei compared to intact fellow eyes.
Keywords: oftalmodek; okomistin; cornea; apoptosis; cytotoxicity; infection; antiseptics